Balancing the solar irradiance needs: optimising growth in sphagnum palustre through tailored UV-B effects - JiaYue Sun; Ling Xu; Lian Liu; BeiBei Huang; XingYu Liu; JunFeng Xu; Lin Wu (BMC Plant Biology)
Abstract Background The carbon sequestration potential and water retention capacity of peatlands are closely linked to the growth dynamics of Sphagnum mosses. However, few studies have focused on the response of Sphagnum moss growth dynamics to UV-B radiation, and existing research has emphasized species differences. In this study, Sphagnum palustre L., a dominant species in the peatlands of Southern China, was selected as a research subject, and its response to UV-B radiation has not been reported before. Results In the field, the morphology and growth differences of Sphagnum palustre under microhabitats with varying UV-B radiation intensities were monitored. Our findings revealed that the height of Sphagnum palustre increased the most in the microhabitats (Juncus community) with the weakest UV-B radiation, however the capitate branch area and biomass of Sphagnum palustre were highest under the Fern community, where UV-B radiation was attenuated by 50% during the summer. In the laboratory, we established four levels of UV-B radiation treatments: 0 MJ/m2/d (control group, no UV-B radiation), 0.2 MJ/m2/d (low UV-B radiation), 0.4 MJ/m2/d (middle UV-B radiation), and 0.8 MJ/m2/d (high UV-B radiation). We investigated the effects of UV-B radiation intensity on the morphology, biomass, and water-holding capacity of Sphagnum palustre after exposing it to UV-B radiation for 30 days. Results indicated that low UV-B radiation (0.2 MJ/m2/d) significantly enhanced the growth of Sphagnum palustre. The capitulum area, plant height, capitulum biomass, and individual biomass of Sphagnum palustre increased by 14.60%, 1.27%, 10.98%, and 16.49%, respectively, compared to the control. Additionally, the maximum water absorption rate of Sphagnum palustre reached 4515.44%. In contrast, under high UV-B radiation (0.8 MJ/m²/d), these indicators significantly decreased, while the water loss rate significantly increased. Conclusion This study suggests that the intensity of UV-B radiation can be artificially regulated to optimize the growth of Sphagnum, accelerate peatland restoration, and enhance the yield of artificially cultivated Sphagnum moss.